Quality assessment on emergency medical services documentations in trauma cases - Nurumal, Mohd. Said; Aung, Khin Thandar; Jamain, Mohdtaufik (www.journalijar.com, 2017)
Background: The quality assessment would enhance accountability in emergency medical services (EMS) and provide EMS agencies with data to measure their system’s overall performance and to develop sound strategic quality improvement planning. The aim of this study was to determine the quality assessment of emergency medical service documentation for trauma cases. Methods: The quality assessment of emergency medical services (EMS) documentation for trauma cases was conducted in the Emergency Medical Communication Centre, Hospital TengkuAmpuanAfzan (HTAA), Kuantan Pahang. A stratified convenience sampling was used as sampling method and the EMS documentation checklist was adopted by Monash University, Centre for Ambulance and Paramedic Studies. The score of the documentation will be reflected with the health care personnel background. The data were analysed by using (SPSS) version 19.0 for windows. Results: 235(100%) of EMS healthcare personnel had fulfilled the requirement for date, patient details, caller details, police notification and also hospital destination. However, for the medications given, only 15 out of 235 documents were documented and 235 (100%) were excluded the adverse effect and allergic reaction of medication to the patient. The overall mean of the quality assessment documentation was 75.013 while the standard deviation was 11.780. Based on the result shown, there was a significant association between years of employment with the quality assessment (t=-4.01, p<0.001). Conclusion: Only 40% of the documentation were categorised as quality documentations. And only years of employment had significant association with the quality of emergency medical service documentation. Meanwhile, there was no significant association of races and gender with the quality emergency medical service documentation